2021
DOI: 10.1101/2021.09.07.459046
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep sampling of ancestral genetic diversity reveals Saccharomyces cerevisiae pre-domestication life histories

Abstract: The ecology and genetic diversity of model yeast Saccharomyces cerevisiae prior to human domestication remain poorly understood. Taiwan is regarded as part of this yeast's geographic birthplace where the most divergent natural lineage was discovered. Here, we deep sampled the broad-leaf forests across this continental island to probe the ancestral species diversity. We found that S. cerevisiae is ubiquitously distributed at low abundance in the forests. Whole-genome sequencing of 121 isolates revealed nine dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 105 publications
(152 reference statements)
0
2
0
Order By: Relevance
“…Large variations exist in the frequency of sex in yeast (for a review, see Nieuwenhuis & James, 2016). Population genomic methods can be used to estimate the relative frequency of asexual and sexual reproduction by comparing differences in mutation and recombination rates (Friedrich et al, 2015; Lee et al, 2021; Tsai et al, 2008) and have shown population‐level differences (Drott et al, 2020; Koufopanou et al, 2020; Liti et al, 2009; Tsai et al, 2008).…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Large variations exist in the frequency of sex in yeast (for a review, see Nieuwenhuis & James, 2016). Population genomic methods can be used to estimate the relative frequency of asexual and sexual reproduction by comparing differences in mutation and recombination rates (Friedrich et al, 2015; Lee et al, 2021; Tsai et al, 2008) and have shown population‐level differences (Drott et al, 2020; Koufopanou et al, 2020; Liti et al, 2009; Tsai et al, 2008).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Similar surveys also identified other northern hemisphere Saccharomyces species (Sampaio & Gonçalves, 2008). For instance, recent studies suggest that eastern Asia harbors several Saccharomyces species characterized by high genetic diversity (Bendixsen et al, 2021; Bing et al, 2014; Duan et al, 2018; Han et al, 2021; Lee et al, 2021; Peter et al, 2018; Wang et al, 2012), including temperate forest S. cerevisiae populations that are strongly diverged from domesticated populations (Duan et al, 2018; Wang et al, 2012). Some examples of successful sampling efforts that uncovered multiple species include a study in which S. kudriavzevii , S. uvarum , and S. cerevisiae were isolated from oak bark in Portugal (Sampaio & Gonçalves, 2008, 2017), and another in which S. arboricola , S. kudriavzevii , and S. cerevisiae were isolated from mushrooms, litter and leaves in Taiwan (Naumov, Lee, & Naumova, 2013).…”
Section: Model Yeast Genera In Temperate Forestsmentioning
confidence: 99%